Awaiting Education: Friedrich Nietzsche On the Future of Our Educational Institutions - Allen, Ansgar (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
The republication of Nietzsche’s lectures “On the Future of Our Educational Institutions” invites reconsideration of Nietzsche’s thought on education. Though there is much in these lectures that might appeal to those struggling for the future of the humanities, or for the future of education more generally, I argue against their use in the attempted redemption of the humanities or education. Consideration of “Schopenhauer as Educator”, published two years later, brings out Nietzsche’s growing hostility to education. Education in modernity is a lost cause, Nietzsche argues. It is beyond redemption because (1) true teachers can no longer be found and (2) we are almost incapable of educating ourselves. At best we might attempt to educate ourselves against the age, which includes the challenging task of educating against our selves. From this position, which holds out little hope for the future of education as it is currently configured, if the modern educator has any functionality left, it is to serve as a symptom of decline.